Clinical characteristics and prognosis of steroid-resistant nephrotic syndrome in children: a multi-center retrospective study - Sheng Li; Chao He; Yu Sun; Jie Chen; Yunguang Liu; Zengpo Huang; Weifang Huang; Yongqiu Meng; Wenjing Liu; Xianqiang Lei; Rihong Zhao; Zihui Lin; et al. (BMC, 2024)
Abstract Background This study investigated the factors influencing the prognosis of children with steroid-resistant nephrotic syndrome (SRNS) in patients from the Guangxi region. Methods We retrospectively analyzed clinical and pathological data of 279 patients with SRNS from six tertiary hospitals in Guangxi. Clinical data were compared between initial (I-SRNS) and secondary (S-SRNS) steroid resistance subgroups and Cox regression analysis was used to determine risk factors for chronic kidney disease (CKD) and CKD stage 5 (CKD5) in patients with SRNS. Results The median age of onset was 54 months. Thirty-three patients had extra-kidney manifestations. Fifty-two, 24, 57, 33, and 41 patients had hypertension, acute kidney injury, vitamin D deficiency, high intraocular pressure, and dwarfism, respectively. One hundred eighty-two and 92 patients had I-SRNS and S-SRNS, respectively. There were significant differences in sex, ethnicity, family history, incidence of hematuria, clinical classification, efficacy of immune agents, and prognosis between groups (P < 0.05). Among the 279 cases of SRNS, 239 had normal kidney function, 37 developed CKD, and 16 had CKD5. An increase in serum creatinine level (HR = 1.003) was significantly associated with CKD in children with SRNS, and effective immunosuppressant therapy decreased the CKD risk (HR = 0.168). Patients with increased serum creatinine levels (HR = 1.003) and acute kidney injury (HR = 4.829) were more likely to progress to CKD5. Conclusions Children with S-SRNS showed a higher response to immunosuppressants than those with I-SRNS. Effective immunosuppressant therapy was found to protect against CKD, whereas increased acute kidney injury was an independent risk factor for CKD5.